Analysis of the technology of disposal of chicken litter - Grigorenko, Serhii; Григоренко, Сергій Михайлович; Григоренко, Сергей Михайлович (НУБіП України, 2021)
EN : The main characteristics of dust furnaces: Meet the most stringent environmental standards; combustion with zero CO and extremely low NOx; Complete combustion of biomass (100% biological composition); Efficiency, stability and controllability are the same as those of a natural gas furnace. Able to operate simultaneously on a mixture of fuels: powder, liquid, gaseous. Noise level less than 85 dBa (decibels); Compact design, which makes the furnaces much smaller and cheaper than with other technologies; These dust stoves have been used in industry for over 35 years and have proven to be highly efficient and reliable.
Keywords: drying mechanism; тhe kinetic energy; mechanical forces; rotor; mass transfer coefficient